Detailed studies on seed oil of Salicornia SOS-7 cultivated at the egyptian border of Red Sea - El-Mallah, M. Hassan; Turui, T.; El-Shami, S. (Grasas y Aceites, 1994)
Eight lipid patterns of Salicornia seed oil have been elucidated using HPLC as the main tool of analysis in conjunction with capillary GLC. The whole oil is rich in linoleic (66.5%) with lower amount of linolenic acid (1.4%). Of the 22 triglycerides (TG) determined, three major TG containing 3 and 2 linoleic acyls were detected by HPLC. The total tocopherols content (720 ppm) was determined directly in the oil by HPLC and it was found that alpha-T (49.1%) and gamma-T (48.2%) are predominating. The whole sterol profile, as determined by GLC, includes cholesterol (1.0%), brassicasterol (1.4%), campesterol (2.4%), 5-stigmasterol (8.7%), beta-sitosterol (23.0%), spinasterol (17.0%), isofucosterol (0.8%), 7-stigmastenol (42.0%) and 7-avenasterol (3.7%). Furthermore, sterols patterns of the free (nonacylated) sterols (FS), acylated sterols (AS), free sterylglycosides (FSG) and acylated sterylglycosides (ASG) were determined by HPLC as their anthroylnitriles. FS and AS were determined as their steryl-9-anthroylnitriles (S-9-AN) whereas FSG and ASG were analysed as their sterylglycosidyl-1-anthroylnitriles (SG-1-AN) at nanogram level. Comparing Salicornia SOS-7 oil with traditional freshwater seed oils, Salicornia exhibits mostly a unique lipids constitution.